Chromosomally-Encoded Yersinia pestis Type III Secretion Effector Proteins Promote Infection in Cells and in Mice - Schesser Bartra, Sara; Lorica, Cherish; Qian, Lianfen; Gong, Xin; Bahnan, Wael; Barreras Jr., Henry; Hernandez, Rosmely; Li, Zhongwei; Plano, Gregory V.; Schesser, Kurt (Frontiers in Cellular and Infection Microbiology, 2019)
Yersinia pestis, the causative agent of plague, possesses a number of virulence mechanisms that allows it to survive and proliferate during its interaction with the host. To discover additional infection-specific Y. pestis factors, a transposon site hybridization (TraSH)-based genome-wide screen was employed to identify genomic regions required for its survival during cellular infection. In addition to several well-characterized infection-specific genes, this screen identified three chromosomal genes (y3397, y3399, and y3400), located in an apparent operon, that promoted successful infection. Each of these genes is predicted to encode a leucine-rich repeat family protein with or without an associated ubiquitin E3 ligase domain. These genes were designated Yersinia leucine-rich repeat gene A (ylrA), B (ylrB), and C (ylrC). Engineered strains with deletions of y3397 (ylrC), y3399 (ylrB), or y3400 (ylrA), exhibited infection defects both in cultured cells and in the mouse. C-terminal FLAG-tagged YlrA, YlrB, and YlrC were secreted by Y. pestis in the absence but not the presence of extracellular calcium and deletions of the DNA sequences encoding the predicted N-terminal type III secretion signals of YlrA, YlrB, and YlrC prevented their secretion, indicating that these proteins are substrates of the type III secretion system (T3SS). Further strengthening the connection with the T3SS, YlrB was readily translocated into HeLa cells and expression of the YlrA and YlrC proteins in yeast inhibited yeast growth, indicating that these proteins may function as anti-host T3S effector proteins.